ELEX and EGEX: Euroclassica Certificates in Latin and Greek - John Bulwer (The Journal of Classics Teaching)
One of the initiatives of Euroclassica (the federation of European associations of Classics teachers) is to set a yearly test for Latin and Greek: European Latin Exam (ELEX) and European Greek Exam (EGEX). They are both available at beginners’ level (Vestibulum) and intermediate level (Ianua). Schools can set and correct them in their own time and award Euroclassica certificates as appropriate. The tests are available in English, French and German, but individual associations and schools are free to translate them into their own languages. Candidates are advised to take the tests at any age when they are ready; there is no charge. This article outlines the procedure and gives examples of the texts and questions set. The example questions are given in more than one language to illustrate the European nature of the enterprise, with an extra taste of how far ELEX and EGEX can spread in the example of questions in the Macedonian language from North Macedonia. Schools should contact their national association for more local information. Yearly results, past papers and more information are published in the Euroclassica newsletter available on the website: https://www.euroclassica.eu/portale/euroclassica.html